2014
DOI: 10.4236/ajps.2014.513203
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Water Deficit and Phosphorus Application on Phosphorus Uptake and Yield of Soybean (<i>Glycine max</i> L.) at Dejen, North-West Ethiopia

Abstract: A green house experiment was conducted at Dejen, Northwest Ethiopia, with the objective of quantifying the critical soil water deficit and P levels that affect yield and yield components of soybean, and determine the critical soil water deficit levels influencing P uptake in soybean. The treatment consisted of factorial combination of four available soil water (ASW) deficit levels (0%, 25%, 50% and 75%) and four levels of phosphorus (0, 10, 20, and 30 kg•ha −1 ) laid out in RCBD with four replications using so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
4
10
0
Order By: Relevance
“…The highest P concentrations were determined at the control treatment (3.0 g kg -1 ) and drought stress induced decreases in P concentrations were observed in this study. Results are also in agreement with those reported by Getachew (2014). In the study, P concentrations decreased with increase in water deficit level.…”
Section: Resultssupporting
confidence: 93%
“…The highest P concentrations were determined at the control treatment (3.0 g kg -1 ) and drought stress induced decreases in P concentrations were observed in this study. Results are also in agreement with those reported by Getachew (2014). In the study, P concentrations decreased with increase in water deficit level.…”
Section: Resultssupporting
confidence: 93%
“…These results suggested that the response of the phenological period to the amount of irrigation depended on the levels of irrigation and cultivars. This finding is in agreement with Getachew (2014), who concluded that water deficit might hasten or delay phenological periods depending on the time it occurs, severity, rate of onset of the stress, and type of species involved. On the other hand, the days to reach the R8 stage in 2017 was delayed more than in 2016, probably due to delayed stem senescence.…”
Section: Discussionsupporting
confidence: 92%
“…Our results support previous findings reported by Basal and Szabó (2020) and Jin et al (2006). Similarly, results disclosed here are in agreement with previous work (Getachew, 2014;Jin et al, 2006).…”
Section: Phosphorus Uptake In Soybeansupporting
confidence: 94%